Review Legal To Comments on Social Media Containing Element Harassment and Assault Psychics in Maros City - Adriansyah, Andi Muhammad; Razak, Azkari; Ilham, M. Azham (COMPENDIUM OF JUDGE MADE LAW, 2025)
This research aims to find out and analyze the qualifications for commenting on social media which contain elements of harassment and psychological attacks in criminal acts, knowing and analyzing the judge's legal considerations in deciding case No.14/Pid.Sus/2023/Pn. Mrs. This research was conducted in Makassar City. The research location is the Library of the Faculty of Law, Indonesian Muslim University. This writing was carried out by conducting a literature study in which the author studied by prioritizing the theories that are currently being applied while at the same time obtaining documents or data related to the problem in the author's writing which was then processed and presented descriptively by the author. The results of this research show that in qualifying comments In social media that contains elements of harassment, it is classified as an attack on honor or good name. Based on the Decision of the Panel of Judges No.14/Pid.Sus/2023/Pn.Mrs, the defendant has been proven to have committed the crime of Defamation. After the author examines the decision, the author is of the view and/or opinion that the decision of the panel of judges is appropriate and in accordance with the law because in fact, the elements of the article in which the defendant is accused meet the elements that the author has described.